Predicting working beyond retirement in the Netherlands: an interdisciplinary approach involving occupational epidemiology and economics - Micky Scharn; Allard J van der Beek; Martijn Huisman; Astrid de Wind; Maarten Lindeboom; Chris TM Elbers; Goedele A Geuskens; Cécile RL Boot (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: No study so far has combined register-based socioeconomic information with self-reported information on health, demographics, work characteristics, and the social environment. The aim of this study was to investigate whether socioeconomic, health, demographic, work characteristics and social environmental characteristics independently predict working beyond retirement. METHODS: Questionnaire data from the Study on Transitions in Employment, Ability and Motivation were linked to data from Statistics Netherlands. A prediction model was built consisting of the following blocks: socioeconomic, health, demographic, work characteristics and the social environment. First, univariate analyses were performed (P0<.15), followed by correlations and logistic multivariate regression analyses with backward selection per block (P0<.15). All remaining factors were combined into one final model (P0<.05). RESULTS: In the final model, only factors from the blocks health, work and social environmental characteristics remained. Better physical health, being intensively physically active for >2 days/week, higher body height, and working in healthcare predicted working beyond retirement. If respondents had a permanent contract or worked in handcraft, or had a partner that did not like them to work until the official retirement age, they were less likely to work beyond retirement. CONCLUSION: Health, work characteristics and social environment predicted working beyond retirement, but register-based socioeconomic and demographic characteristics did not independently predict working beyond retirement. This study shows that working beyond retirement is multifactorial.